A harmonic suppression strategy for grid-connected inverters based on quadrature sinewave extractor - Xia, Yan; Feng, Zetao; Chen, Renzhao; Wu, Jie; Huang, Qinyuan (Frontiers in Energy Research, 2022)
Grid-connected inverters need to reduce current harmonics as much as possible. After introducing the input signal’s fundamental and main harmonic quadrature components, a discrete state model is created, and the discrete observer design method is used to propose a harmonic extraction algorithm called quadrature sinewave extractor (QSE). The QSE is a stable recursive operator with the advantages of no phase displacement and the ability to eliminate mutual influence between harmonic components. Compared to the widely used proportional multi-resonant controller, QSE can reduce current harmonics and improve system stable performance by using it in the current control of grid-connected inverters. Finally, comparative experiments on a three-phase grid-connected inverter are used to verify the proposed method’s effectiveness.